Bruzzano river mouth damage due to meteorological events. Issue 4 (2nd October 2022) - Canale, Caterina; Barbaro, Giuseppe; Foti, Giandomenico; Petrucci, Olga; Besio, Giovanni; Barillà, Giuseppina Chiara
ABSTRACT: The Italian territory, due to its geomorphological and climatic characteristics, is particularly prone to hydrogeological instability phenomena such as flash floods, river floods, sea storms and coastal erosion. These phenomena are particularly relevant due to the considerable Italian coastline, of about 8300 km in length, and to the presence of many rivers. The most critical aspects of these phenomena are observed in the case of concurrent events. The paper describes an event of hydrogeological instability which occurred in 2015 in Bruzzano Zeffirio, a town in southern Ionian Calabria. The event consisted of both a flood, which caused the flooding of the Bruzzano river, a torrential river, and a sea storm. The joint action of both phenomena may have also caused the collapse of the highway bridge and of the railway bridge, both located near the river mouth. The paper analyses the possible correlations between this event and the geomorphological and climatic characteristics of the study area. It represents a pilot study on the conditions that favour the contemporaneity between floods and sea storms and can be extended to other territories with the same characteristics. Also, this study can be used by a local administrator to plan and manage these territories.